Soil campodeids (Diplura, Campodeidae) of Eastern Europe, in Romanian and Bulgarian reliefs - Alberto Sendra; Cristina Fiera; Jesús Selfa; Pavel Stoev (ZooKeys)
This study presents data on soil campodeids collected in Romania and Bulgaria in recent years. The collection comprises 12 species of genus Campodea Westwood, 1842 in total. A new species, Campodea (Dicampa) transylvanica Sendra, sp. nov. is described from Zarand and Făgăraș mountains in Romania. Campodea (Campodea) plusiochaeta Silvestri, 1912 is newly recorded for the Romanian fauna, while Campodea (Paurocampa) ruseki Condé, 1966 represents a new record for Bulgaria. New distributional data are also provided for the remaining ten species.